Coach humour styles and athlete commitment: A relational mediation model in team sport contexts - Egemen Merdan, H.; Çaglar, E. (Kinesiology, 2025)
Humour, often viewed as a light-hearted communicative tool, carries important relational significance in elite sport. Affiliative humour has the potential to build trust and cohesion, whereas aggressive humour may threaten relational safety and undermine athlete engagement. While humour has been widely studied in organizational psychology, its implications in sport coaching remain underexplored. This study examined how athletes` perceptions of coaches` humour styles influence motivational commitment through the mediating mechanisms of relationship quality - closeness, commitment, and complementarity - guided by Humour Styles Theory, the 3+1 Cs Model, and the Sport Commitment Model. Participants were 341 athletes (aged 18-35) from five team sports in Türkiye. Measures assessed perceptions of coaches` affiliative and aggressive humour, coach-athlete relationship quality, and two forms of sport commitment: enthusiastic and constraint commitment. Regression-based mediation analyses tested indirect effects of humour styles on commitment through relational dimensions. Results indicated that affiliative humour was positively associated with enthusiastic commitment, fully mediated by athletes` perceptions of commitment and complementarity, but not by closeness. In contrast, aggressive humour predicted lower levels of enthusiastic commitment, both directly and indirectly through weakened perceptions of commitment and complementarity. Neither humour style showed significant associations with constraint commitment. These findings suggest that affiliative humour strengthens athletes` motivation by reinforcing task-relevant relational dynamics, whereas aggressive humour undermines them. In performance-driven contexts, functional alignment may be more influential than emotional closeness. Coach education programmes should therefore encourage the intentional use of affiliative humour as a relational strategy to sustain athlete engagement and long-term commitment.